PERANCANGAN APLIKASI PEMBELAJARAN ON-LINE BERBASIS E-LEARNING PADA SMP ISLAM NURUL IKHSAN - Kania, Raden; Umam, Chotibul; Sumarti, Winda (Teknik Informatika Fakultas Ilmu Komputer, 2018)
Design of application learning methode online basic e-learning for Smp Islam Nurul Ikhsan is an innovation for SMP Islam Nurul Ikhsan to improve learning conditions. There are two very crucial backgrounds for making this web e-learning. First, the weakness of the learning patterns (face-to-face learning in the classroom) that is used by SMP Islam Nurul Ikhsan. Second, the development of technology that has advanced rapidly by the stageholder need to think of education to improve learning conditions. giving the task in this application is a program in which these programs with each other are interconnectedso that the computer will automatically do the processing of the data entered into the system. The main objectives contained in this final is Design of Application Learning Methode On-Line Basic E-Learning For SMP Islam Nurul Ikhsan.The analytical method used in the design and development of this application is the language of program used PHP and database mySql. Application learning method on-line basic e-learing this was made in order to fasilitate the smooth teaching and learning activities to students and teacher and improve the human resources of the world of the internet, so it can improve the performance and quality of schools. The result is the availability of application supporting teaching and learning activities that can be accessed on-line. This web based application add facilities teachers and students in terms of communicating, given the subject matter, administration and collection teks, and add facilities in the information value.